2020
DOI: 10.1016/j.nicl.2020.102351
|View full text |Cite
|
Sign up to set email alerts
|

Atypical response inhibition and error processing in 22q11.2 Deletion Syndrome and schizophrenia: Towards neuromarkers of disease progression and risk

Abstract: Highlights We tested response inhibition in 22q11.2DS and schizophrenia. We show reduced P3, Ne, and Pe responses in 22q11.2DS and schizophrenia. P3 was only reduced when psychotic symptoms were present. Ne and Pe were reduced regardless of the presence of symptoms. P3 may be a marker of disease severity, Ne/Pe might be markers of risk.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 128 publications
(171 reference statements)
0
7
1
Order By: Relevance
“…A previous study on visual processing in 22q11.2DS reported early (~100 ms) visual processing reductions (53). In that study, however, no distinction was made between those with and without psychotic symptoms, a distinction that we have shown to be highly relevant (55,56). And indeed, here, the increased amplitudes between 90 and 140 ms in 22q11.2DS appear to be mainly driven by those without psychotic symptoms (see Figures 5 and 6A).…”
Section: Schizophrenia and Controlscontrasting
confidence: 45%
See 1 more Smart Citation
“…A previous study on visual processing in 22q11.2DS reported early (~100 ms) visual processing reductions (53). In that study, however, no distinction was made between those with and without psychotic symptoms, a distinction that we have shown to be highly relevant (55,56). And indeed, here, the increased amplitudes between 90 and 140 ms in 22q11.2DS appear to be mainly driven by those without psychotic symptoms (see Figures 5 and 6A).…”
Section: Schizophrenia and Controlscontrasting
confidence: 45%
“…While these support the presence of visual processing differences in 22q11.2DS that, descriptively, partially recapitulate those seen in schizophrenia, no differentiation was made between those with the deletion and psychotic symptoms and those with the deletion and no psychotic symptoms. The importance of this distinction is apparent from our previous work (55,56), in which we demonstrated significant differences in both cognitive and neural function between these two groups. Moreover, the focus on this population and subsequent differentiation between those with and without psychotic symptoms allows one to hypothesize about potential markers of risk/vulnerability for psychosis versus of disease.…”
Section: Introductionmentioning
confidence: 72%
“…One often-used approach to studying response inhibition is the Go/NoGo task using a set of visual images as stimuli. The task requires pressing a response button after each novel image is presented ('Go' trial), but withholding the button press in response to the second presentation of a repeated image ('NoGo' trial) [15,23,29,[42][43][44][45][46][47][48]. During successful NoGo trials during which the participant properly withholds a response, two stimulus-locked Event-Related Potential (ERP) components are typically elicited: the N2 and the P3.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies using different paradigms (visual, visuospatial memory and phonological tasks) reported a positive correlation of P300 amplitude reduction with an impairment in different cognitive abilities, such as visual attention [ 156 , 203 , 250 ], working memory [ 204 , 206 ], self-referential memory [ 207 ], language processing [ 206 ] in SCZ and with executive functioning in both SCZ and at-risk subjects [ 205 ]. Interestingly, a study that focused on the predictive value of ERPs in the efficacy of the combination of two cognitive remediation programs showed that higher baseline P300 amplitude values were associated with greater improvements in attention, memory and speed of processing [ 93 ].…”
Section: Resultsmentioning
confidence: 99%